O controle nas companhias abertas brasileiras de capital pulverizado - Garcia, Letícia Simonetti (2008)
This paper focuses on the capital pulverization phenomenon in Brazilian corporations and the effects arising therefrom in terms of control power organization in the light of Law No. 6404, enacted on December 15, 1976 ( LSA Corporation Law), its possible consequences, and proposes feasible solutions for conflicts that may surface in this new scenario. For this purpose, control power in joint stock companies was analyzed according to the manner it is regulated in the LSA, its diverse classifications, characteristics, and outstanding implications, as well as the bodies within joint stock companies that are directly affected as a result of capital pulverization in corporations, the concepts that act as guidelines for corporate governance in Brazil and, finally, the company s social role. Based on these studies, control in corporations with pulverized capital was submitted to a critical examination in order to assess if existing legal rules and mechanisms in our laws are adequate for the new reality. The intention was to demonstrate with this thesis that capital pulverization will demand adjustments to LSA and/or to the regulations of the CVM (Securities and Exchange Commission) and of the differentiated markets of corporate governance regarding the diverse control implications in a joint stock company with pulverized capital so as to ensure legal security which is essential for the continuous growth of our capital market and, ultimately, for our economy